1985
DOI: 10.1063/1.95807
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and formation mechanism of porous silicon

Abstract: A systematic study is presented of the effects of silicon dopant type, resistivity, current density, and hydrofluoric acid concentration on the formation and properties of porous silicon. Cross-section transmission electron microscopy revealed the presence of two distinct microstructures. The structure formed is determined by the doping level with the transition occurring near degeneracy. A model of the anodisation process is presented which is based on the semiconducting properties of the material and which e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
2
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(108 citation statements)
references
References 2 publications
6
98
2
2
Order By: Relevance
“…For a (001)-oriented PS sample, it is generally admitted that the pores have a cylindrical shape with lateral branching (Beale et al, 1985). The long axis of the cylindrical shape is parallel to the h001i direction, i.e.…”
Section: Study Of Thick Ps Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…For a (001)-oriented PS sample, it is generally admitted that the pores have a cylindrical shape with lateral branching (Beale et al, 1985). The long axis of the cylindrical shape is parallel to the h001i direction, i.e.…”
Section: Study Of Thick Ps Layersmentioning
confidence: 99%
“…There are still some controversies regarding the pore size and morphology, and more particularly concerning the pore-propagation direction, which is the result of a competition between the current-¯ow direction and the crystallographic directions. In 1985, in a cross-sectional transmission electron microscopy (XTEM) study on p + -and p À -type (respectively highly and slightly boron-doped) PS layers, Beale et al (1985) showed pore propagation perpendicular to the wafer surface, i.e. along the current direction.…”
Section: Introductionmentioning
confidence: 99%
“…This argument was supported in the literature, from the chemical composition studies of PS layer, using IR spectroscopy measurements showing that the silicon surface is terminated with hydrogen, although the Si-F (6 eV) bond is much strong than Si-H bond. 7,12,14,[18][19][20][21][22][23][24] Figure 1 shows top view images of typical PS samples prepared by photoelectrochemical oxidation of n-type silicon, etching time of 60 min and current density of 11 mA cm -2 . The samples were prepared with two different solutions of HF-ethanol and HF-MeCN, for two types of Si resistivity.…”
Section: Resultsmentioning
confidence: 99%
“…It was in order to make a detailed study of models proposed to explain the morphology found in n-type silicon (Smith et ai. 1988, Beale et al 1985a, b, Erlebacher et al 1994, including the formation of side branches and the reaction of the system to changes in the applied potential, that we decided to examine the pore formation process in real time.…”
Section: Anodic Etching Of Siliconmentioning
confidence: 99%